Sistem Pemesanan Online Warung Sate Berbasis Web Menggunakan Waterfall - Haydar Ahadya Al Mansuri; Raya Yuni Setiawan; Indyah Hartami Santi (Teknologi Informasi : Teori, Konsep, dan Implementasi : Jurnal Ilmiah, 2025)
Warung Sate Ayam dan Kambing Pak Risziam faces challenges in maintaining its existence amid intense competition in the culinary industry. The main challenges stem from the use of traditional systems in ordering, stock management, and marketing strategies that are considered inefficient and hinder business development in the digital era. This research aims to design and implement an integrated online reservation system that combines digital ordering with structured financial management using the waterfall development model methodology. This model includes sequential and systematic stages of requirement analysis, system design, implementation, testing, and maintenance. The development results in a digital platform that facilitates customers in placing orders, reduces staff workload, and provides electronic transaction recording systems to improve accuracy in financial management. The implementation of this system becomes a strategic step in building solid digital infrastructure that supports the sustainability and growth of Warung Sate Pak Risziam amid the technology-based transformation of the culinary industry.